Browning the archive: troubling normative formations of South African *Indian Identity - Singh, Zenaéca (Michaelis School of Fine Art, 2026)
My study engages South African *Indian historiography through a gendered lens. Available archival material is largely owed to the colonial governance of the immigration of Indians as indentured labourers and passengers. Accordingly, *Indian women were sidelined and defined by colonial and patriarchal structures that constructed them as chaste and subservient wives and daughters. However, they were also exoticized and deemed as deviant and immoral for causing outbreaks of gender-based violence, venereal diseases, and infant mortality in indentured communities. Therefore, notions of *Indian womanhood was largely overdetermined by the colonial and male gaze. Decolonial strategies of destabilization are critical to this study to subvert the visual and discursive regimes of *Indians. This study responsively centers the position of women to decipher their sense of agency as opposed to passivity. I therewith consider an artistic practice that combines an engagement with archival and personal material to expose the sublime violence and erasures of the past whilst filling in these gaps of history. Browning is an alternative term for referring to the complexity and hybridity of the South African *Indian identity outside of its normative formations. Through the indenture narrative and the aesthetics of sugar I work through historic and familial events that can help visualize and speculate a sense of the lived experience of South African *Indians or being Brown.